(untitled) (International Journal of Engineering and Computer Science, 2017)
Friction Stir Welding (FSW) was invented by Wayne Thomas at TWI (The Welding Institute), and the first patent applications were filed in the UK in December 1991, that utilizes a non-consumable rotating welding tool to generate frictional heat and plastic deformation at the welding location; there by, affecting the formation of a joint while the material is in the solid state. Friction stir welding (FSW) is the latest technology in the area of metal joining and is perhaps the most promising of all the welding processes. A lot of research has been carried out in this area but most of the initial work has been done on low temperature softening materials like aluminium alloys. Friction Stir Welding (FSW) has become a major joining process in the railway, aerospace, auto industries and ship building industries especially in the fabrication of aluminium alloys. The process uses a spinning non-consumable tool to generate frictional heat in the work piece. This paper looks at the review, on friction stir welding process, various welding variables like tool rotation, transverse speed, tool tilt, plunge depth and tool design, for the welding of aluminium alloys or various dissimilar alloys. Applications are also described.